Fruit production and post harvest handling project - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This project for the production and post-harvest handling of fruits is supports the agricultural diversification efforts of the Ministry of Agriculture and is in keeping with the Agricultural Development Plan which focus on diversification of the sector. The development of this document is consistent with IICA's thrust in terms of its support of initiatives for agricultural development of the region.